Generasi Z dan Brain Drain : Apa yang Mendorong Talenta untuk Pergi? - Elisa Eliyani Putri (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
The brain drain phenomenon in generation Z has become a significant global issue. This research aims to explore the factors that encourage generation Z to leave their home countries to seek opportunities abroad. Using a case study-based qualitative approach, data was collected through in-depth interviews and focus group discussions with respondents aged 18-27 years. Thematic analysis identified four main themes: economic opportunity, educational quality, socio-political dissatisfaction, and self-development aspirations. The results show that intrinsic motivation, such as the desire for self-development and multicultural experiences, plays an important role in addition to external factors such as educational quality and economic opportunities. These findings highlight the need for policy strategies to create conditions that support young people to continue contributing in their home countries.